2005
DOI: 10.1038/sj.onc.1208580
|View full text |Cite
|
Sign up to set email alerts
|

TRAIL sensitizes for ionizing irradiation-induced apoptosis through an entirely Bax-dependent mitochondrial cell death pathway

Abstract: The death ligand TRAIL has been suggested as a suitable biological agent for the selective induction of cell death in cancer cells. Moreover, TRAIL synergizes with DNAdamaging therapies such as chemotherapeutic drugs or ionizing irradiation (IR). Here, we show that synergy of TRAIL and IR, that is, crosssensitization between TRAIL and IR for induction of apoptosis, entirely depends on Bax proficiency in human DU145 and HCT116 carcinoma cells. DU145 prostate carcinoma cells that have lost Bax protein expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0
1

Year Published

2005
2005
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 62 publications
2
46
0
1
Order By: Relevance
“…The critical role of both Bak and Bax during apoptosis induction by p14 ARF is further underlined by the observation that their combined loss completely impaired mitochondrial activation, as evidenced by the failure of Bax/Bak double-deficient cells to release cytochrome c upon p14 ARF expression. This is in clear contrast to other proapoptotic stimuli, that is, death receptor ligands such as TRAIL (von Haefen et al, 2004;Wendt et al, 2005) or the BH3-only proteins Nbk (Gillissen et al, 2003) or Puma (Yu et al, 2003) that completely rely on the presence of Bax, but not Bak, to facilitate the activation of mitochondria and subsequent execution of apoptotic cell death in human cancer cells. Consequently, we observed that epirubicininduced apoptosis occurred in a predominantly Baxdependent manner in our systems.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The critical role of both Bak and Bax during apoptosis induction by p14 ARF is further underlined by the observation that their combined loss completely impaired mitochondrial activation, as evidenced by the failure of Bax/Bak double-deficient cells to release cytochrome c upon p14 ARF expression. This is in clear contrast to other proapoptotic stimuli, that is, death receptor ligands such as TRAIL (von Haefen et al, 2004;Wendt et al, 2005) or the BH3-only proteins Nbk (Gillissen et al, 2003) or Puma (Yu et al, 2003) that completely rely on the presence of Bax, but not Bak, to facilitate the activation of mitochondria and subsequent execution of apoptotic cell death in human cancer cells. Consequently, we observed that epirubicininduced apoptosis occurred in a predominantly Baxdependent manner in our systems.…”
Section: Discussionmentioning
confidence: 97%
“…Proapoptotic Bak is controlled preferentially by Bcl-x L and Mcl-1 until released by proapoptotic signals, that is, by Noxa (Mcl-1) and Bad (Bcl-x L ) (Willis et al, 2005). These proteins appear to play selective roles, which may delineate a higher degree of specificity to the regulation of Bax and Bak in p14 ARF -induced cell death in analogy to other apoptosis-promoting stimuli (Theodorakis et al, 2002;Gillissen et al, 2003;Yu et al, 2003;von Haefen et al, 2004;Wendt et al, 2005), which clearly demands further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Bax, but not Bak, sensitized leukemic and prostate cancer cells to TRAIL. 35,36 PKCe-deficient LNCaP cells were sensitive to PMA-induced apoptosis and forced expression of PKCe in these cells conferred resistance to PMA-mediated apoptosis via interaction with Bax. 34 We have shown that the levels of antiapoptotic Bcl-2 as well as proapoptotic Bid were regulated by PKCe in MCF-7 breast cancer cells, whereas PKCe had no effect on the level of Bax.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have implicated Bax as an important mediator of cellular responsiveness to TRAIL. 16,34,35 Bax-deficient colon cancer cells were resistant to TRAIL-induced apoptosis. 2 Bax, but not Bak, sensitized leukemic and prostate cancer cells to TRAIL.…”
Section: Discussionmentioning
confidence: 99%